AB0027 Screening for antibody reactivity in early axial spondyloarthritis identifies novel antigenic targets. (12th June 2018) - Quaden, D.; Vandormael, P.; Corten, K.; Vanhoof, J.; Geusens, P.; Somers, V.
Abstract : Background: Diagnosis of axial spondyloarthritis (axSpA) is challenging since clinical manifestations, such as inflammatory back pain, peripheral arthritis, enthesitis and inflammatory bowel disease, often overlap with other disorders. Despite the use of the genetic marker Human Leukocyte Antigen (HLA)-B27 in axSpA patients, an appropriate serological test is still lacking. Although antibodies are not considered to be a hallmark of axSpA, emerging evidence suggests plasma cells and antibodies to be involved in the disease course 1 . Objectives: Our aim is to screen for antibodies reactive against antigenic targets in plasma of early axSpA patients which may potentially result in novel antibody biomarkers to improve axSpA diagnosis and can enhance the assessment of disease activity, prognosis and therapy response. Methods: We applied Serological Antigen Selection (SAS), un unbiased and high-throughput antibody profiling procedure based on cDNA phage display. First, a cDNA phage display library was constructed from synovial hip tissue from 3 axSpA patients and screened for antibody reactivity in pooled plasma of early axSpA patients (n =10 ). By performing SAS, we identified antibodies in the axSpA plasma pool that were reactive against 104 different antigenic targets. These targets correspond to both known proteins and novel lineair peptides. In a first validation, antibody reactivity against each of these 104 SAS-identified targets was determined in pooled plasma of additional early axSpA patients (n =50 ) and healthy controls (HC, n =30 ). Antigenic targets that showed highest reactivity in axSpA plasma pools were further validated in individual plasma samples of early axSpA patients (n =71 ) and HC (n =73 ) using phage enzyme-linked immunosorbent assay (ELISA). Results: Increased antibody reactivity against 7 targets was found in pooled plasma of additional early axSpA patients. Further validation of these 7 antigenic targets in individual plasma samples revealed antibody reactivity in 39% of the early axSpA patients (28/71) compared with 21% of the HC (15/73). By forming a biomarker panel with 4 of these targets, specificity could be improved to 88% (9/73 HC) with only a slightly decrease in sensitivity (34%, 24/71). Conclusions: We identified autoantibody reactivity to novel antigenic targets in early AS patients. In order to establish the true biomarker potential, antibody reactivity against our identified novel antigenic targets will be further validated in an independent cohort of axSpA patients, rheumatic controls and low back pain controls. Identification of antibody reactivity against novel antibody targets in early axSpA patients can contribute to novel biomarkers for an enhanced diagnosis and might provide more insight into the underlying disease pathology, resulting in novel treatment strategies and eventually improve disease outcome in axSpA patients. Reference: [1] Quaden D, et al. Autoimmun Rev. 2016Aug;15(8):820–32. Acknowledgements: We thank the orthopaedic surgeons from Hospital East-Limburg, Jessa Hospital and Maastricht University Medical Centre for providing synovial tissue, rheumatologists from ReumaClinic for sample collection and Kim Ulenaers and Igna Rutten (Hasselt University Biomedical Research Institute) for processing the samples and technical support. Disclosure of Interest: None declared